Index Options: The Early Evidence - Evnine, Jeremy; Rudd, Andrew (Journal of Finance, 1985)
Index options became the most important traded contracts during their first year of existence. Two contracts, namely those on the S&P100 and the Major Markets Index, have a trading volume which typically surpasses the trading volume in all individual stock option contracts. In this paper, we examine the pricing of the options on the S&P100 and the Major Markets Index. Using intra-day prices, we find the options frequently violate the arbitrage boundary, put/call parity, and are substantially mispriced relative to theoretical values. Our results suggest that tests of option pricing models may be more difficult than previously realized due to nonsynchronous prices, even using “real-time” data from the exchanges.